Penerapan Sak Etap Pada Bumdes Arum Jaya Mandiri Desa Jambearum Kecamatan Puger Kabupaten Jember - Firda Novianti Afkarina; Diyah Probowulan; Astrid Maharani (CV. Ulil Albab Corp, 2022)
Implementation of SAK ETAP in BUMDes Arum Jaya Mandiri Jambearum Village. The purpose of this study was to analyze the application of SAK ETAP in BUMDes Arum Jaya Mandiri Jambearum Village. This type of research is qualitative descriptive. Primary data can be obtained from direct sources, secondary data from intermediary media. The financial statements of BUMDes Arum Jaya Mandiri only make statements of financial position and profit and loss statements per the end of accounting period, this is not in accordance with the provisions of SAK ETAP. Completeness in the presentation of the Arum Jaya BUMDes financial report which should follow the reference to SAK ETAP is still lacking. The information submitted by the compilers of financial statements is still lacking so that it can be used as material for performance evaluation in its preparation for the future.